Simple Additive Weighting for Prioritizing the Allocation of Health Product Promotion Areas at Sari Medika Primary Clinic - Dian Prawitasari,; Setiawan, Aries; Lely Kusumaningrum,; Ichwan Setiarso,; Moch. Sjamsul Hidajat,; Andi Hallang Lewa,; Dedi Joko Purnomo,; Karmila, (Jurnal Transformatika, 2026)
One of the supporting elements of clinical services is the fulfillment of the space with the specified function. One of the health service spaces designated by the government is the education and training room, which is the health product promotion area. At the Sari Medika Main Clinic, this space is called the health product promotion area. The increasing demand for use of this area creates its own problems, especially related to the window of interest. Prioritization of loans is needed by not only looking at a single variable but rather a combination of several supporting factors for loans. The method required is a simple additive weighing using multicriteria and weighting for each variable. The final result of this study is a drain rate of 85%, so it can be used as an alternative in finding the priority of users of this area